The Wetu Telu Community’s Customary Chief Influence on the Management of Indigenous Forests in Bayan, North Lombok, West Nusa Tenggara - Jayadi, Edi Muhamad; Khairi, Akhmad Khalakul; Sutasoma, Muwardi (Department of Forestry, Faculty of Agriculture, University of Lampung, 2024)
The existence of an institution system and customary chief is very important for the sustainability of customary forest management. This study attempts to explain the function of the traditional chief of Wetu Telu community in the management of indigenous forests in the Bayan Sub-District, North Lombok Regency, West Nusa Tenggara Province, as well as the institutional framework and changes in that function. Observation, interviews, and documentation were used to collect data. The data obtained was analyzed thematically using Nvivo 12 Software, while a descriptive analysis used the Milles and Huberman Model. The results show that customary chiefs have the following roles: raise public awareness, spearhead conservation efforts, convey moral and spiritual messages, guide and oversee conservation efforts, mediate conflicts of interest related to nature, lead religious activities related to nature, and establish communication and collaboration. The institutional system of the Wetu Telu community’s customary chief consists of several components, including special requirements, an appointment mechanism, personnel, a term of office, a source of income, and a dismissal mechanism. The role of the customary chief in indigenous forest management continues to be strengthened from time to time. The reasons for strengthening the role of the customary chief are the issuance of the Constitutional Court Decision Number 35 of 2012 concerning the status of indigenous forests, the recognition of the success of local wisdom-based forest management patterns, increasing public awareness of the importance of environmental conservation, global warming, and, the development of ecotourism. Keywords: customary chief, indigenous forest management, local government, Wetu Telu community